Exploring Kinase Inhibition Properties of 9H-pyrimido[5,4-b]- and [4,5-b]indol-4-amine Derivatives - Yvonnick Loidreau; Carole Dubouilh-Benard; Marie-Renée Nourrisson; Nadège Loaëc; Laurent Meijer; Thierry Besson; Pascal Marchand (MDPI AG, 2020)
We previously highlighted the interest in 6,5,6-fused tricyclic analogues of 4-aminoquinazolines as kinase inhibitors in the micromolar to the nanomolar range of IC50 values. For the generation of chemical libraries, the formamide-mediated cyclization of the cyanoamidine precursors was carried out under microwave irradiation in an eco-friendly approach. In order to explore more in-depth the pharmacological interest in such tricyclic skeletons, the central five member ring, i.e., thiophène or furan, was replaced by a pyrrole to afford 9H-pyrimido[5,4-b]- and [4,5-b]indol-4-amine derivatives inspired from harmine. The inhibitory potency of the final products was determined against four protein kinases (CDK5/p25, CK1δ/ε, GSK3α/β, and DYRK1A). As a result, we have identified promising compounds targeting CK1δ/ε and DYRK1A and displaying micromolar and submicromolar IC50 values.